PCR-RFLP Analysis of D-Loop mtDNA in Indonesian Domestic Waterfowl - R Susanti; Fidia Fibriana; Ari Yuniastuti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Phylogenetic or population genetic studies have been focused on finding genetic variations in mitochondrial DNA (mtDNA) because mutations in this region contained five times higher than other genetic materials. The aim of this research was to generate PCR-RFLP D-loop mtDNA profiles of some Indonesian domestic waterfowl. The samples were 35 local ducks, 5 muscovy duck, and 5 geese. These local ducks included on seven types of Javanese ducks in Central Java, i.e. Magelang duck, Peking duck, Pengging duck, Tegal Branjangan duck, Tegal Jarakan duck, Tegal Blorong duck, and Tegal Lemahan duck. PCR technique was used to amplify the D-loop genes, and RFLP analysis of the D-loop was performed with AluIand RsaI. The results show that muscovy duck has no restriction sites in D-loop gene. Moreover, goose has a restriction site of AluI in D-loop gene at 550 bp and 187 bp; and it has no restriction site of RsaI. The analysis of RsaI-RFLP in mtDNA D-loop region of ducks resulted in 1 restriction fragment pattern which can be applied in the identification of duck to differentiate it from goose and muscovy duck. PCR-RFLP analysis duck D-loop mtDNA using AluI and RsaI restriction enzyme resulted in 3 combinations of restriction fragment pattern shown in 3 haplotypes (A, B, and C). Genetic diversity of Indonesian domestic waterfowl population could be identified by using PCR-RFLP analysis on mtDNA D-loop region. So far, there are few results of research on Indonesian domestic waterfowl genetic characteristics based on PCR-RFLP mtDNA D-loop marker. Also, this research has a good contribution on genetic characterization of local duck. The characterization is an important aspect to maintain breed quality and manage the genetic resources of Indonesian germplasm and in facilitating the breeding program.